CONSUMER BEHAVIOR DAN MARKETING MIX - Agus Hasan Pura A (Bina Ekonomi, 2005)
Marketing concept emerged since business philosophy shifted to a customer-centered, the job is to find the right products for your choosen target markets. The reason for customer orientation in which all functions work together to respond to, Serve, and satisfy customer. To satisfy consumer (end user) the marketing concept use integrated marketing, that is segmenting, Targeting, positioning, and marketing mix (4p/7p). And to.be success, marketer have to understand the behavior of consumers of her or his target market. The understanding of consumer's behavior helps to formulate the right and the effective marketing mix to satisfy consumers better than competitors.